Student Character Building on Metaphor in Raja Ali Haji’s and Robert Herrick’s Poems - Dewi Masitho Istiqomah (Universitas Muhammadiyah Jember, 2019)
The metaphor is figurative language that compares something with other things that has similar characteristics. Character building is the way to build mental of a person to be better especially in their personality aspect such as how to love his or her country, respect the difference, etc. The best way to conduct personality is an education by interesting educational personality in teaching learning. The descriptive qualitative research method is used to identify or describe the process and get deep understanding from those poems. After analyzing the data, it was found that 31 metaphors are used in these poems such as structural metaphor (4), orientational metaphor (17), and ontological metaphor (10), and also fifty data of character building from poem were found, including religious, tolerant, and patriotic characters.